IMPLIKATUR PERCAKAPAN SEBAGAI TINDAK KOMUNIKATIF PADA NOVEL HIDAMARI NO KANOJO - Dormauli, Pronika Periati; Rahayu, Nana; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: In the pragmatics, meaning or purpose that appear in a speech called implicatures. Implicatures that appear of two or more people who is conversing with each other called conversational implicature. The purpose of this research is to describe the implicatures of conversations in the Hidamari No Kanojo novel. Besides that, it also aimed to explain the purpose of the communicative acts on it. Theory that used were Grice (1975) to find out kind of implicatures conversational according to flouting of maxim in the coorperative principle and Brown (1980) about communicative acts. This research is a qualitative descriptive method to decribing the data in the Hidamari No Kanojo novel. The results of this study were (1) found general conversational implicatures as much as 12 data, the special conversational implicatures as many as 8 data (2) mean of conversational implicatures by the speakers explained through the communicative acts which is classified into 15 types according to their intended purpose.Key Words: Implicatures, Coorperative Principle, Communicative Acts, Novel, Pragmatics.